PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM SISWA KELAS V SEKOLAH DASAR NEGERI 36 PEKANBARU - ', Riapamiliani; ', Zulkifli; ', Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated by the low IPA learning results of students, with an average grade 62.42. While the value of minimum completeness criteria (KKM) IPA is 70. Among the students who totaled 29 people only 11 students with classical completeness KKM reached 39.29%. This study is a Classroom Action Research (CAR) conducted aims to improve learning outcomes fifth grade science students of SD Negeri 36 Pekanbaru to implement cooperative learning model of Jigsaw. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This paper presents the study results obtained average results of study before action increased 10.25% 62.24 into 68.62 in cycle I. In the second cycle increased by 17.17% to an average of 72.93. Application of learning models koopeatif Jigsaw can increase the activity of teachers in the first cycle the first meeting 66.6% percentage obtained with enough categories, At the second meeting experience becomes 79.16%. Furthermore, the first meeting of the second cycle teachers activity score increased by 83.3% good category, at the second meeting an increase of 4.16% to 91.66% with the good category yet. Application of Jigsaw cooperative learning model can improve the activity of students in the first cycle to 66.6% in the category enough, at the second meeting 76.16% In this cycle the students already understand the learning activities with the implementation of Jigsaw cooperative. And the second cycle student activity score increased by 87.5% good category. At the second meeting increased to 91.67% with the good category yet. Results of the study in class V SDN 36 Pekanbaru prove that the implementation of cooperative learning model of Jigsaw can improve learning outcomes fifth grade science students of SDN 36 Pekanbaru.Keywords : cooperatif type jigsaw, the result of IPA